Non-marine Animal Bioactive Peptides. Properties, Sources, and Applications - Chamorro, Verónica Celeste; Pazos, Adriana Alejandra; Báez, Jessica; Fernández-Fernández, Adriana Maite; Medrano, Alejandra (Springer Nature, 2024)
Animal proteins and their derivatives play a fundamental role in human nutrition as a source of valuable nutrients and bioactive peptides that have shown an increased interest for their application in the food, pharmaceutical, medicine, and cosmetics industry. In the past years, animal peptides have increased their application in the pharmaceutical industry, due to their great versatility, varied pharmacological functions, high specificity, and low levels of toxicity as well as being natural compounds with minor or no adverse effects when compared to synthetic drugs. Strikingly, only some of the bioactive peptides are sold on the market as functional foods. The possible reason is that most of them do not have sufficient evidence in terms of efficacy and food safety. Additionally, different processing methods may have a certain impact on their bioavailability, affecting their application in food. Therefore, several encapsulation methodologies are being studied in order to protect bioactive peptides, enhance their bioavailability as well as to enhance their sensory and physicochemical properties. This chapter summarizes current knowledge on peptides from meat, milk, and eggs, the main methods of obtaining peptides (enzymatic hydrolysis with commercial proteases, fermentation, and gastrointestinal digestion) and their bioactive properties (antihypertensive and cardiovascular health improvement, antioxidant, antidiabetic, antiobesity, antitumor activity, gut, and neurological health improvement). Moreover, peptide bioaccessibility and bioavailability studies will also be discussed, since these are key factors for these compounds to exert their mechanisms of action in the body. Finally, a discussion about the food applications and perspective studies for promoting animal bioactive peptides use is carried out. In sum, the full set of reported bioactivities plus future research on the efficacy and safety through clinical studies, coupled with the efficient use of byproducts for a sustainable production of these peptides, will reveal the full scope of potential applications of these natural molecules.